An analysis of performance appraisal system in Shurugwi district day secondary schools - Gudyanga, Ephias; Shumba, P.; Wadesango, N. (Kamla-Raj, 2016)
The study was designed to find out if there was a clear policy on the execution and implementation of performance appraisal system as well as a clear understanding of the use of the system and its proper implementation by both the appraiser and the appraisee. The study adopted a quantitative research approach. Systematic random sampling was used to come up with schools to be involved. Stratified sampling was also used to come up with the number of teachers and heads respondents. For data collection, questionnaires were used. Frequency table percentages pie chart was used. Results indicated that there is a policy on performance appraisal although it was not written down for all implementers. There is a fair understanding of the performance appraisal implementation and its uses. The study concluded that administrators and teachers did not know the model of performance appraisal. It was recommended that there be more effort by policy –decision makers to ensure that the policy on the performance appraisal system be available to all stations where the system is being used.